Equality
In this case, we'll have to carry out several steps to find the solution.
Step 01:
Data
sec θ - sinθ tanθ = cos θ
prove the identity = ?
Step 02:
We must use the trigonometric identities to find the solution.
sec θ - sinθ tanθ = cos θ
![\frac{1}{\cos\text{ }\theta}-\sin \theta\cdot\frac{\sin\text{ }\theta}{\text{cos}\theta}=\cos \text{ }\theta](https://img.qammunity.org/2023/formulas/mathematics/college/yfweicbat50ql1ee4ovqnxtz7nzyrv3mph.png)
![(1)/(\cos\theta)-(\sin^2\theta)/(\cos\theta)=\cos \theta](https://img.qammunity.org/2023/formulas/mathematics/college/mjo72fkpv48fu0ls9if2b6ls7gckzy4xny.png)
![(1-\sin^2\theta)/(\cos\theta)=\cos \theta](https://img.qammunity.org/2023/formulas/mathematics/college/4tliluldtz0xdtqou000zj6yukzm256f5u.png)
![(\cos^2\theta)/(\cos\theta)=\cos \theta](https://img.qammunity.org/2023/formulas/mathematics/college/4aud4mqeqhfgbt6ve97vzzb3jm4mbufqla.png)
![\cos \text{ }\theta\text{ = cos }\theta](https://img.qammunity.org/2023/formulas/mathematics/college/huhdaukfbnxm23ds5gdnqsabf8e57ynxri.png)
The answer is:
Equality is verified.
cos θ = cos θ